Emulsifying properties of novel biopolymer (Cola acuminata gum) extracted from pods of Cola acuminata: Macroscopic, Microscopic and Rheological Characterization - Bamigbola Emmanuel Adelaja; Oraeluno Jude Nkemjika; Victor Ola Ade (German Journal of Pharmaceuticals and Biomaterials, 2023)
Gums are valuable excipients usually employed as emulsifiers in the preparation of pharmaceutical, food and cosmetic products. The emulsifying properties of Cola acuminata gum (CAG) derived from the pods of Cola acuminata were evaluated. Different batches of emulsions containing arachis oil (40% v/v) emulsified with distilled water were formulated respectively with tragacanth gum (TRG), acacia gum (ACG) and CAG at different concentrations (1.0-4.0% w/v). The different formulations were labelled as TRG1-TRG4, ACG1-ACG4 and CAG1-CAG4. Organoleptic properties real-time and accelerated stability studies of the emulsions were evaluated using centrifugation, thermal and freeze-thaw conditions. The rheology of the emulsions was measured using a Digital Synchroelectric viscometer (NDJ- 5S, China) with spindle 2 operated at various rotational speeds (6, 12, 30 and 60 rpm). In contrast, the microstructures of the emulsions were evaluated by photomicrography. CAG1, TRG1 and ACG1-ACG4 could not form stable emulsions. Real-time stability studies revealed that TRG2 and CAG2 cracked on days 3 and 7, respectively. TRG3 experienced creaming from the fourth week, while TRG4, CAG3 and CAG4 remained unchanged. Accelerated stability tests induced creaming in CAG3 and TRG4. The degree of creaming induced by various accelerated stability conditions was in the order of thermal > freeze-thaw > centrifugation. CAG4 showed no creaming throughout the experiment. All the emulsions exhibited pseudoplastic behaviour. There was no significant change in the viscosity of TRG3, TRG4, CAG3 and CAG4 after 8 weeks of storage. An increase in the concentration of the emulsifiers increased the emulsions' viscosity and stability. There was an increase in the emulsions' droplet size and a decrease in emulsions' droplet number during storage, indicating gradual coalescence. CAG showed superior emulsifying properties.